Religious rite and ceremony in Milton's poetry - Stroup, Thomas B. (Thomas Bradley), 1903- (Lexington : The University Press of Kentucky, 2015)
Milton, the arch-Puritan and outspoken critic of the stereotyped rituals of the established churches, has been regarded by most scholars as a writer who is unlikely to have employed liturgical materials in his poetry. Thomas B. Stroup shows to the contrary that Milton made extensive use of Christian liturgy not only as material within the body of his poems but also as a force in shaping them. In a survey of both Milton's major works and his minor poems, prayers of thanksgiving, the General Confession, similarities to hymns, echoes from canticles, and many other rites and ceremonies of the churc.
Cover; Title; Copyright; Preface; Acknowledgments; Contents; Introduction; 1. The Minor Poems; 2. Paradise Lost; 3. Paradise Regained; 4. Samson Agonistes; Conclusion; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; V.
Print version record.
Keywords: Christian poetry, English -- History and criticism; Christianity and literature -- England -- History -- 17th century; Milton, John, -- 1608-1674 -- Religion; Rites and ceremonies in literature; POETRY -- English, Irish, Scottish, Welsh; POETRY / English, Irish, Scottish, Welsh; Electronic books